Universal decimal classification. UDC 687 Clothing industry. Beauty culture industries (BSI, 1984)
Universal Decimal Classification, Classification systems, Clothing, Industries, Textile machinery and accessories, Cosmetics, Hairdressing, Fur, Brushes, Brooms